2000
DOI: 10.1203/00006450-200001000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in Breast Milk from Allergic and Nonallergic Mothers

Abstract: The allergy-preventing effect of breast-feeding remains controversial, possibly because of individual variations in the composition of the breast milk. The aim of this study was to investigate the concentrations of cytokines involved in allergic reactions and IgA antibody production in breast milk from allergic and nonallergic mothers. The cytokine concentrations were determined in colostrum and 1-mo. milk samples from 24 mothers with, and 25 mothers without, atopic symptoms, using commercial ELISA kits. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
163
1
9

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(182 citation statements)
references
References 34 publications
9
163
1
9
Order By: Relevance
“…We detected lower TGF-β and sCD14 in breast milk samples of overweight subjects as compared with those from normal-weight subjects. This finding may mirror a T helper 2-polarized responder type previously reported to be associated with the allergic state of the lactating mother, found from comparing colostrum samples from allergic mothers with those from nonallergic mothers (20). Correspondingly, the counts of Bifidobacterium-group bacteria were lower whereas those of Staphylococcus-group microbes and Akkermansia muciniphila levels were higher in milk samples of overweight mothers than in those of normal-weight mothers.…”
Section: Maternal Bmi Impact On Milk Componentsmentioning
confidence: 48%
See 1 more Smart Citation
“…We detected lower TGF-β and sCD14 in breast milk samples of overweight subjects as compared with those from normal-weight subjects. This finding may mirror a T helper 2-polarized responder type previously reported to be associated with the allergic state of the lactating mother, found from comparing colostrum samples from allergic mothers with those from nonallergic mothers (20). Correspondingly, the counts of Bifidobacterium-group bacteria were lower whereas those of Staphylococcus-group microbes and Akkermansia muciniphila levels were higher in milk samples of overweight mothers than in those of normal-weight mothers.…”
Section: Maternal Bmi Impact On Milk Componentsmentioning
confidence: 48%
“…The same evolution pattern was seen in our study with respect to sCD14 and IL6. The latter are associated with reduction in risk of allergy, atopic dermatitis, asthma, and obesity (18,19) and with indirect anti-inflammatory potential via stimulation of IgA synthesis (16,20). The correlations between the concentrations of cytokines involved in IgA synthesis, i.e., IL-10, IL-6, and TGF-β, may explain the stimulatory effect on IgA production in breast-fed babies (20).…”
Section: Discussionmentioning
confidence: 99%
“…32 It has been shown that atopic mothers have higher levels of T H 2 cytokines (IL-4, IL-5, and IL-13) compared with nonatopic mothers. 33,34 These differences may result in different IgE levels in the child, which may contribute to risk of allergies. 8 Work in mice has shown that breast milk is sufficient but not necessary to mediate allergenindependent maternal transmission of asthma to the offspring.…”
Section: Discussionmentioning
confidence: 99%
“…20 Breast milk concentration of sIgA was measured after the thawed, stored samples had been centrifuged at 25,000 RCF for 30 minutes at 4°C to remove the lipid layer. 21 All samples were processed in the same way without access to information about the other laboratory and clinical findings. The supernatants were diluted 1:5000 in sterile saline solution or PBS just before use.…”
Section: Methodsmentioning
confidence: 99%